An Effective Teaching and Learning Approach for the Architectural Program with Reference to the Framework of Educational Psychology - Nurakmal, Abdullah@ Goh Tuo Ho; Surat, M.; Mazlan, Mohd Tahir; Muhammad, Nor; Utaberta, Nangkula (Elsevier Science, Ltd., 2011)
The development of architecture in Malaysia is facing a crisis due to various problems perpetuated by individuals or groups related to the field. The individuals and groups mentioned are also categorized as human capital which not only consist of the technocratic group but also of various background disciplines such as contractors, suppliers, developers, patrons, entrepreneurs, lawyers and others. The problem is caused by the weakness of the human capital which is produced by the educational institution. Since there are opinions about a crisis which the education institution is facing in its teaching programme, it seems unsuccessful in its role in producing quality human capital. The approaches and ways of teaching and learning should be changed. It should be referred to the opinion of educational psychologists and professional academicians to upgrade the quality of teaching and learning explicitly on the architectural program.